SELF-MENTIONS IN CLIMATE CHANGE DISCOURSE BY KING CHARLES III (Journal of Contemporary Philology, 2024)
Climate change discourse provides a fertile ground for research in communication, linguistics, and discourse studies (Grist 2008; Isopp 2024; Nerlich et al. 2010). Anchored in a quantitative linguistic paradigm, the article presents a mixed-methods study on the use of self-mentions (for instance, I, we, etc.) in a corpus of speeches on the topic of climate change delivered by King Charles III. The study aims at establishing the frequencies of the occurrence of self-mentions and learning about their pragmatic roles in the corpus. To that end, the corpus of King Charles III’s speeches on climate change was collected and analysed. The results of the corpus analysis indicated that I was the most frequent self-mention, which King Charles III utilised in order to impart a personalised dimension to his discourse on climate change. The findings and their discussion are further presented in the article.
Keywords: a corpus-assisted study; climate change discourse; King Charles III; self-mentions